The morphodynamic response of a gravel barrier to unimodal and bimodal storm wave conditions - Ions, Kristian; Ozdemir, Khan; Pender, Douglas; Reeve, D. E.; Karunarathna, Harshinie (Frontiers in Marine Science, 2023)
Gravel barrier beaches can offer natural protection to coastlines from adverse storm conditions. Understanding the morphodynamics of gravel barrier beaches is vital for the effective and sustainable management of these systems. Here, we use a synthetic dataset to investigate the morphodynamic response of the gravel barrier beach at Hurst Castle Spit, located on the Southwest coast of the United Kingdom, to both unimodal and bimodal storms. This spit is exposed to wind and swell waves propagating up the English Channel from the Southwest approaches and has suffered repeated storm erosion. The results are analyzed to identify the key drivers that govern the spatio-temporal gravel barrier morphodynamic responses to storms and to explore the morphodynamic states of the barrier. We found that the morphodynamic response of the barrier beach is strongly influenced by the combination of storm wave height and still water level. Further, the presence of swell waves can be a controlling factor in the barrier response.